New technique of identifying the hierarchy of dynamic domains in proteins using a method of molecular dynamics simulations - Yesylevskyy, S.O. (Вiopolymers and Cell, 2010)
Despite a large number of existing domain identification techniques there is no universally accepted method, which identifies the hierarchy of dynamic domains using the data of molecular dynamics (MD) simulations. The aim of this work is to develop such technique. Methods. The dynamic domains are identified by eliminating systematic motions from MD trajectories recursively in a model-free manner. Results. The technique called the Hierarchical Domain-Wise Alignment (HDWA) to identify hierarchically organized dynamic domains in proteins using the MD trajectories has been developed. Conclusion. A new method of domain identification in proteins is proposed. Незважаючи на велику кількість існуючих підходів до ідентифікації доменів у білках, на сьогодні немає єдиного загальновизнаного методу, який міг би визначати ієрархію динамічних доменів на основі даних молекулярної динаміки. Метою роботи є створення такого методу. Методи. Домени визначають рекурсивним елімінуванням систематичних рухів у траєкторіях молекулярної динаміки. Результати. Розроблено новий метод визначення ієрархії доменів на основі даних молекулярної динаміки, який отримав назву ієрархічного доменного вирівнювання (HDWA). Несмотря на большое количесто существующих подходов к определению доменов в белках, на сегодня нет единого общепризнанного метода, с помощью которого можно было бы идентифицировать иерархию динамических доменов на основе данных молекулярной динамики. Целью работы является разработка такого метода. Методы. Домены определяют рекурсивным элиминированием систематических движений в траекториях молекулярной динамики. Результаты. Создан новый метод определения иерархии доменов на основе данных молекулярной динамики, получивший название иерархического доменного выравнивания (HDWA).